Optimized Synthesis Conditions of Ionic Liquid-Silica Using Response Surface Methodology - Lee, Y.R.; Tian, M.; Row, K.H. (Asian Journal of Chemistry, 2014)
To develop the methodology of the surface coverage of ionic liquid -silica, conditions of the synthesis were optimized using the fractional factorial design with three-variables and three-levels by a response surface methodology computer program. Variables, such as the amount of silica (g), volume of silane (mL) and amount of imidizole (g), were investigated. The following optimum conditions were derived by response surface methodology: amount of silica = 20 g, volume of silane = 0.1 mL and amount of imidazole = 0.53 g. The theoretical surface coverage of ionic liuqid-silica (0.382) was obtained under the above conditions using the Design-Expert software.